Alignment of Policies, Standards, and Guidelines for Teacher Education Programs with the K to 12 Program - Gonzales, Richard DLC (Animo Repository, 2024)
This study investigated the role of Teacher Education Institutions (TEIs) in facilitating the evaluation of students in the K to 12 Program, specifically in examining the alignment between teacher education Policies, Standards, and Guidelines (PSGs) and the K to 12 Program assessment. Results revealed that the PSGs on teacher education have minimal congruence with the K to 12 curriculum standards and principles on student assessment. Despite this, a commendable focus within the PSGs is evident, emphasizing developmentally appropriate, relevant, and research-based approaches to student assessment aligned with 21st-century skill development. However, the absence of articulation regarding the majority of K to 12 curriculum standards and principles related to student assessment underscores a significant gap, necessitating a comprehensive revision and expansion of the PSGs to ensure they effectively address these essential aspects and remain congruent with the changing educational environment and the demands of the K to 12 program. Therefore, this policy analysis emphasizes the importance of ongoing curriculum development to guarantee the thorough integration of all elements of the K to 12 program's assessment philosophy into teacher education PSGs, promoting a more inclusive and holistic approach to education.